The Routledge Handbook of European Integrations (Taylor & Francis, 2022)
CAP; Common Market; EDA; Erasmus; European integration; European Armament; CERN; European media; Eurozone; ITER; European tourism
English
Keywords: Politics & government; CAP; Common Market; EDA; Erasmus; European integration; European Armament; CERN; European media; Eurozone; ITER; European tourism